2017
DOI: 10.1038/ni.3796
|View full text |Cite
|
Sign up to set email alerts
|

α-ketoglutarate orchestrates macrophage activation through metabolic and epigenetic reprogramming

Abstract: Glutamine metabolism provides synergistic support for macrophage activation and elicitation of desirable immune responses; however, the underlying mechanisms regulated by glutamine metabolism to orchestrate macrophage activation remain unclear. Here we show that the production of α-ketoglutarate (αKG) via glutaminolysis is important for alternative (M2) activation of macrophages, including engagement of fatty acid oxidation (FAO) and Jmjd3-dependent epigenetic reprogramming of M2 genes. This M2-promoting mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
664
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 828 publications
(756 citation statements)
references
References 46 publications
27
664
2
3
Order By: Relevance
“…In addition, further analysis suggested that αKG inhibited inflammation response in macrophage through epigenetic reprogramming. These findings are consistent with other studies that αKG regulated the immune responses of macrophages through metabolic and epigenetic reprogramming . Our previous study had determined that melatonin inhibited inflammasome formation and pyroptosis in adipocytes .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, further analysis suggested that αKG inhibited inflammation response in macrophage through epigenetic reprogramming. These findings are consistent with other studies that αKG regulated the immune responses of macrophages through metabolic and epigenetic reprogramming . Our previous study had determined that melatonin inhibited inflammasome formation and pyroptosis in adipocytes .…”
Section: Discussionsupporting
confidence: 93%
“…There exists a substantial amount of evidence supporting that melatonin can accelerate key enzymes of the Kreb's cycle and the respiratory chain. Among the known metabolites, αKG has been reported to be essential for the elicitation of desirable immune responses . Recent studies also confirm that melatonin elevates cellular αKG level and prevents α‐ketoglutarate dehydrogenase activation in liver and kidney .…”
Section: Discussionmentioning
confidence: 88%
“…Alternately, α‐KG can be transferred to macrophages by exosomes (Figure A) . Indeed, α‐KG restricts M1 activation by intervening with the NF‐κB pathway via PHD‐mediated post‐translational modification of IKKβ (Figure A) . In LPS‐stimulated M1 macrophages, glutamine metabolism contributes to the accumulation of succinate via anaplerosis (proceeding through α‐KG) and the γ‐aminobutyric acid (GABA) shunt .…”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%
“…Additionally, α‐KG promotes M2 activation by Jmjd3‐dependent demethylation of H3K27 on the promoter of M2‐specific marker genes and improves oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO), which are necessary for M2 macrophage polarization (Figure ) . Indeed, M2 macrophages favor α‐KG accumulation by inhibiting α‐KG dehydrogenase (α‐KGDH) activity .…”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%
See 1 more Smart Citation